RASIO ALBUMIN KREATININ URIN SEBAGAI DETEKSI DINI GANGGUAN FUNGSI GINJAL PADA DIABETES MELITUS - Selvy Laocta Afera; Setyo Dwi Santoso; Rahajoe Imam Santosa (Jurnal SainHealth, 2021)
Diabetes Mellitus is a group of metabolic diseases of impaired glucose intolerance that is closely related to renal vascular breast milk degener abnormalities that begin with the presence of microalbuminuria. Increased serum creatinine levels indicate impaired kidney function. Serum microalbuminuria and creatininelevels are important tocheck because they are indicators of the course of diabetes mellitus. The goal of this study was to examine the ratio of albumin-creatinine urine in people with diabetes mellitus can be used as an early detection of impaired kidney function and see an association between the ratio of urinary creatin albumin and serum creatinine levels. The urine albumin examination method uses immunoturbidimetric assay using the Jaffe method. The subjects of the examination were dm sufferers who conducted fasting blood glucose and HbA1c examinations at Pramita Clinic Laboratory Surabaya. From the results of the study obtained the ratio of albumin creatin urine and serum creatinine in people with DM mostly showed an increase in the ratio of urinary creatin creatin of 117.10 mg / g, while the average results of serum creatinine examination are still within the normal limit, which is 1.0 mg / dl. From this study proves that examination of the ratio of creatin creatin urine can be used as an early detection of kidney function disorders. Keywords: diabetes mellitus, microalbumin urine, serum creatinine